Investment merger efficiency evaluation of energy enterprises: From a perspective of energy internet - Deng, Yirui; Cao, Guiling; Wei, Zhifei; Xu, Xiaofeng; Ma, Li; Gao, Guowei (Frontiers in Environmental Science, 2022)
Evaluating the efficiency of energy enterprises’ investment merger in the energy Internet sector can be a visual measure of the effectiveness of their investment merger in this sector. It is crucial for energy enterprises to achieve strategic transformation and expand their market share. To this end, this study aims to investigate the efficiency of energy enterprises’ investment merger in the energy Internet sector by constructing an efficiency evaluation index system and evaluation model with the characteristics of the sector. Based on which the TOPSIS model is used to distinguish the differences in the efficiency of the same enterprises’ investment merger in different years. The results of the validation on international power enterprises show that the size of the enterprise has an important influence on its investment merger efficiency in this field. In addition, the evaluation index system and method constructed prove to be effective in evaluating and differentiating the annual investment merger efficiency of energy enterprises in the energy Internet field.